Properties study of a local bentonite as an additive in oil and gas industry - Man, Sarimah; Junin, Radzuan; Samsuri, Ariffin; Mohamed Osman, Adil (2000)
This paper present the results of local bentonite potential as an additive in an oil and gas industry study. Two area of sampling had been study, Andrassy and Mansuli of Sabah. A standard addivite of Wyoming bentonite had been used for potential comparison. The study includes mineralogical, chemical composition, cation exchange composition and Atterberg limit. The results show that bentonite sample from Mansuli area is close to the Ca-montmorillonite, sample from Andrassy area is close to plastic kaolin, while Wyoming bentonite is a Na-montmorillonite. However the Na-content in a local bentonite and its CEC value increased after dry and wet treatment process. In general, local bentonite has a potential to be used as an additive in oil and gas industry through treatment process, particularly dry cation exchange process. Therefore, the total cost of oil and gas well development will be reduced since the additive is a local material.